Use of vibrio harveyi bacteria to control luminous bacterial disease in shrimp (Penaeus monodon fabricius) - Centina, Reynaldo S. (Iloilo College of Fisheries and Ocean Sciences, U. P. in the Visayas, 2004)
Different stages of larvae (nauplii ; protozoa ; Mysis) and post larvae (PLI and PL5) of Penaeusmonodon were subjected to bacterin treatments at a concentration of 106cfu/ml. The vaccinated animals were challenged twice with live pathogenic Vibrio harveyi at a concentration of 105 cfu/ml upon reaching the next developmental stage. The mortality rates of the vaccinated and unvaccinated shrimps were recorded 24 hours after bacterial challenge to measure the potency of the bacterin in terms of relative percent survival rate (RPS). Highest protection afforded by the bacterin was found in PL5 vaccinated for 6 hours and challenged in PL10 and PL15 with relative percent survival rates (RPS) of 84.31% and 80.77%, respectively. However, the protection rendered by 4-hour immersion was comparable with RPS values of 66.67% and 73%, respectively. The nauplii vaccinated for 4 and 6 hours were also protected when bacterial challenge was made during protozoa stage with RPS of 62.04% and 63.50%, respectively. The protozoa vaccinated for 6 hours were also protected when challenged in mysis stage (RPS of 60.58%). The protection rendered by bacterin in vaccinated nauplii, protozoa, mysis, PLI and PL5 lasted for 2 days, 4 days, 9 days, 10 days and 10 days respectively. The shrimps immersed in bacterin for 0.5 h and 2 h were insufficiently protected even in vaccinated PL5 stage with RPS values of 21.57% and 45.10%, respectively when challenged in PL 10. Low RPS was also observed when challenge was done in PL15 stage with RPS of 17.31% and 44.23%, respectively. It was evident that bacterin greatly increased the resistance of the larvae and post larvae against the pathogens. Highest survival rates of 77.33% and 89.33% were recorded in PL5 vaccinated for 4 hours and 6 hours and challenged was done in PL10. However, when bacterial challenge was done in PL15, survival rates of 81.33% and 86.67% were also noted. It was evident that vaccination significantly increased survival rates of shrimps from nauplii to PL5 compared with unvaccinated shrimps. Results showed that 4 hours and 6 hours were the optimum immersion time that could better protect the shrimps from V. harveyi. Moreover, the increased resistance to the pathogen was correlated to the time of exposure to the bacterin. The longer the shrimps immerse in bacterin, the greater is the uptake of V. harveyi antigen, which stimulates immune response. This study also showed the potential use of pathogenic V. harveyi which when converted to bacterin could render some protection against its harmful effects in shrimps.
Thesis - [M. S.] - U. P. in the Visayas
Keywords: Bacteria; Shrimps -- Diseases; Vibrio harveyi